Isolation of polymorphic microsatellite markers for the tetraploid Dipteryx odorata, an intensely exploited Amazonian tree species. - Vinson, C; Ribeiro, DO; Harris, S; Sampaio, I; Ciampi, A (2009)
Dipteryx odorata is an intensely exploited Amazonian tree legume. Microsatellite markers were developed to study the genetic structure, gene flow and reproductive biology of D. odorata. Eight highly polymorphic microsatellite markers were isolated from enriched repeat libraries screened for microsatellite repeats. An average of 16 alleles and 0.964 phenotype diversity per locus were found in 76 individuals from the Tapajos National Forest, in the state of Pará in the Brazilian Amazon.